Advances in Mineral Processing and Hydrometallurgy: 2nd Edition - Corby G. Anderson; Hao Cui (Metals, 2024)
After a very successful initial debut, this second edition of a Special Issue of Metals has been commissioned that is specifically devoted to aspects of mineral processing and hydrometallurgy [...]